PSYCHOLOGICAL STUDY OF DESTRUCTURE OF FAMILY RELATIONS - Kayumova , G.N (Educational Research in Universal Sciences, 2024)
This article presents the causes of family disputes, several problems and their psychological solutions and conclusions.